Pre-Operative Dietary Optimization Using Curry Leaves (Murraya Koenigii) Extract with Orange Juice in Severe Anemia: A Case Report - Nawaz S, Mohammed; Basha V, Sadullah; S, Prashanth (Indian Journal of Integrative Medicine, 2026)
Anemia is a common clinical condition frequently encountered in integrative medical practice. This case report describes the use of curry leaves (Murraya koenigii) extract with orange juice as a supportive dietary intervention in a patient with anemia and type 2 diabetes mellitus. The middle-aged woman with menorrhagia secondary to uterine adenomyosis, along with systemic hypertension and diabetes mellitus, with anemia, was initially unfit for surgical management. As part of integrative care, the patient was advised to consume curry leaf extract mixed with orange juice once daily in the morning for 2.5 months, along with a regular diet. Hematological parameters and glycosylated hemoglobin (HbA1c) were assessed before and after the intervention using standard laboratory methods. Following the intervention, improvements were observed in hemoglobin  (Hb) levels, red blood cell (RBC) count, and other hematological indices. A reduction in HbA1C was also noted. The intervention was well tolerated, with no adverse events reported, and the patient subsequently underwent a hysterectomy successfully. This case report highlights a novel integrative dietary approach using curry leaf extract with orange juice as a treatment for anemia.